2013
DOI: 10.1128/jvi.01052-13
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus UL91 Is Essential for Transcription of Viral True Late (γ2) Genes

Abstract: Human cytomegalovirus-encoded UL91 is a betagamma gene that is essential for viral replication. Here we show that the 111-amino-acid (aa) UL91 protein controls accumulation of true-late (␥2) viral transcripts. The primate betaherpesvirus conserved N-terminal region from aa 1 to 71 is sufficient to fully reconstitute function. Evaluation of viral DNA, RNA, and antigen revealed that UL91 protein is expressed with leaky-late (␥1) kinetics, localizes in the nucleus without influencing viral DNA synthesis, and must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 76 publications
5
56
0
Order By: Relevance
“…It appears that the phenotype of the EBV ⌬BFRF2 mutant is reminiscent of that of the EBV ⌬BcRF1 mutant (18), and like BcRF1, BFRF2 has analogs in beta-and gammaherpesviruses. These observations place the BFRF2 protein together with other EBV, CMV, and MHV-68 genes that have been characterized as being essential for late gene expression (18,(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It appears that the phenotype of the EBV ⌬BFRF2 mutant is reminiscent of that of the EBV ⌬BcRF1 mutant (18), and like BcRF1, BFRF2 has analogs in beta-and gammaherpesviruses. These observations place the BFRF2 protein together with other EBV, CMV, and MHV-68 genes that have been characterized as being essential for late gene expression (18,(26)(27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…These genes are called the beta-gamma genes; ORFs 18,23,24,30,31,34, and 66 from MHV-68 are analogs of HCMV UL79, UL88, UL87, UL91, UL92, UL95, and UL49 and EBV BVLF1, BcRF1, BTRF1, BDLF3.5, BDLF4, BGLF3, and BFRF2, respectively. All these genes, except for MHV-68 ORF23 (34) and, by analogy, EBV BTRF1 and CMV UL88, appear to be involved in the regulation of late gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These five viral ORFs play an important role in activating viral late gene promoters, and it has also been shown that ORF30 and -34 are critical for recruiting RNA polymerase II (Pol II). More recently, studies in cytomegalovirus (CMV), a betaherpesvirus, have demonstrated that the UL79, -87, -91, -92, and -95 genes, homologous to MHV-68 ORF18, -24, -30, -31, and -34, respectively, are also essential for viral late gene expression (18)(19)(20)(21)(22). The evidence strongly suggests that beta-and gammaherpesviruses share a similar mechanism to regulate late gene expression.…”
mentioning
confidence: 94%
“…Precisely how these proteins coordinate to direct late gene expression, including whether they interact with the late gene promoter, remains under investigation. Interestingly, studies on human cytomegalovirus (HCMV), a betaherpesvirus, have shown that UL79, UL87, UL91, UL92, and UL95 (the homologues of ORF18, ORF24, ORF30, ORF31, and ORF34, respectively) are also essential for late gene transcription (13)(14)(15)(16).…”
mentioning
confidence: 99%